Effect of photoexcited carrier density on spin diffusion coefficient and helical spin lifetime - Ryo Tokimitsu; Takachika Mori; Jun Ishihara; Makoto Kohda; Yuzo Ohno; Kensuke Miyajima (Physical Review Research)
We investigate the effect of the photoexcited carrier density on helical spin dynamics using time- and spatially resolved magneto-optical Kerr rotation measurements. The helical spin lifetime is extended by increasing the photoexcited electron spin density because the phase decoherence by spin precession is suppressed owing to a decrease in the spin diffusion coefficient. As a result of the quantitative estimation of the photoexcited carrier density dependence of the spin-orbit parameters, the effect of the decrease in the spin diffusion coefficient on the helical spin lifetime is larger than that due to the modulation of the deviation from the persistent spin helix by optical doping.